The intellectual base and research fronts of LGR5: a bibliometric analysis - Ding, Rong; Tang, Zemin; Xu, Rong; Deng, Zhiming (Frontiers in Research Metrics and Analytics, 2025)
BackgroundLeucine-rich repeat-containing G-protein-coupled receptor 5 (LGR5) is involved in canonical Wnt/β-catenin signaling and is a marker of stem cells in several tissues. It plays an important role in self-renewal, metastasis, and chemoresistance of tumors. The plasticity and potential of LGR5 (+) cancer stem cells could provide therapeutic targets for cancer. However, the data in this field is very limited and requires further investigation.MethodsThis study aimed to explore the status and evolutionary trends of LGR5 research using bibliometric analysis. In total, 2,187 publications were retrieved from the Web of Science Core Collection. The period covered by the articles was from 1999 to 2023. CiteSpace, VOSviewer, R software, and Bibliometric Online Analysis Platform were used for bibliometric analysis and visualization.ResultsThe USA was the most productive country, with the highest centrality and largest single-country publications. The Netherlands was the earliest country to conduct LGR5 research. Cleavers, H from the Hubrecht Institute (KNAW) of the Netherlands was the most influential author as measured by H, G, and M-index values and contributions to the number of publications and citations. Intestinal stem cells were a hot topic, while keywords “LGR5 (+) stem cells,” “inflammation,” and “tumor microenvironment” exhibited the strongest burst in recent years, indicating a significant research focus in the future. Additionally, targeting LGR5 (+) stem cells in a specific phase of cancer and in combination with tumor microenvironment (TME) combination could be a future hotspot.ConclusionResearch on LGR5 continues to develop through active global efforts. This study offers a comprehensive analysis of LGR5 using bibliometric and visual methods, highlighting current research hotspots and potential directions for researchers interested in the field.